Crack Remediation in Cementitious Composites Using Self-Healing Strategies - Singla, Ritika (My University, 2026)
Concrete is a widely utilized construction material owing to its cost-effectiveness, adaptability and capacity to withstand substantial compressive loads. However, its limited tensile strength renders it prone to cracking. These cracks accelerate the entry of water and deleterious substances like sulphates, chloride and carbon dioxide into the concrete, resulting in the corrosion initiation of the protective passive layer of steel reinforcement. As the steel undergoes corrosion, it expands, causing the concrete cover meant to shield it from the environment to spall off, ultimately compromising the safety of the structure and its occupants. Regular maintenance and repair work is necessary to prevent such deterioration, however, conventional methods for repairing cracks often fail to match the properties of the existing material, demonstrate limited long-term effectiveness, and are not ideal for inaccessible or narrow cracks. This research investigates a sustainable, material-integrated approach by exploring chemical-assisted healing for crack-healing for closure of cracks in cementitious structures. The study focuses on three primary strategies for chemical healing- injection-based, dipping-based, and admixture-based approaches, evaluated using various healing agents including sodium silicate (NS), calcium hydroxide (CH), calcium nitrate (CN), and their combinations. In the injection-based approach involved the direct insertion of healing agents into the cracks, enabling localized and controlled healing. In the dipping technique, the cracked specimens were immersed in the healing agent solution, facilitating capillary absorption and internal crack repair, whereas in the admixing approach, the healing agents were directly in the cementitious mix during casting without encapsulation. These treatments were evaluated for their effectiveness in healing cracks, compatibility with the cement matrix, and suitability for field-scale applications. The research utilized different evaluation techniques, incorporating both traditional and advanced non-destructive testing (NDT) tools such as Ultrasonic Pulse Transmission (UPT) and Infrared Thermography (IRT), along with visual inspections, water permeability, sorptivity tests, recovery in compressive strength, and microstructural characterization (FESEM-EDS and XRD). The sensitivity of ultrasonic waves to the change in the elastic properties of the medium through which it propagates is used to monitor the progressive healing of cracks in concrete. An increase in the UPT signal strength with the progression of healing in cracked concrete was used to interpret the condition of the crack. Furthermore, the progression of healing is also effectively captured by an IRT camera, which identifies the healed zones based on surface temperature changes. Together, they provided a dual-mode real-time monitoring platform, offering a holistic understanding of the crack-healing phenomenon. Microstructural analyses revealed deposition of C-S-H gels (NS-treated) and calcite crystals (CN-treated) within cracks, confirming chemical compatibility with the host matrix. Comparative analysis revealed that surface crack sealing was achieved more quickly with dipping methods, while injection techniques provided greater depth of penetration and targeted application, making them more effective for both extensive and localized repairs. Systems utilizing admixtures show potential for developing intelligent self-healing concretes but need further enhancement for accommodating larger crack widths. This study not only confirms the viability of chemical-based strategies for crack healing through effective delivery methods but also underscores the dependability of advanced non-destructive testing (NDT) techniques in measuring healing effectiveness. The results from this research establish a foundation for the creation of automated crack detection and healing solutions, where real-time monitoring using UPT can initiate the controlled release of healing materials, and IRT can illustrate and verify the progress of healing. The approaches and results are adaptable for practical use in the field, such as spraying, injection, or dosing of admixtures, facilitating the development of sustainable and low-maintenance concrete infrastructure.
Keywords: Crack-healing; Ultrasonic Pulse Transmission Monitoring; Chemicals; Healing agents